Changes in free amino acids and polyamine levels in Satsuma leaves in response to Asian citrus psyllid infestation and water stress1. (14th February 2014) - Malik, Nasir S. A.; Perez, Jose L.; Kunta, Madhurababu; Patt, Joseph M.; Mangan, Robert L.
Abstract The effects of biotic and abiotic stresses on changes in amino acids and polyamine levels in Satsuma orange (Citrus unshiu; cultivar Owari) leaves were investigated. Asian citrus psyllids Diaphorina citri (Kuwayama) (ACP) infestation was used to induce biotic stress while a water deficit was imposed to induce abiotic stress. Potted trees were infested by placing 50 psyllids on 3 citrus leaves enclosed in nylon mesh bags for 5 d. A parallel set of plants were kept water stressed by maintaining the soil at 20% water holding capacity for 5 d. Levels of total free amino acids were higher in water stressed and ACP infested leaves. Polyamine putrescine increased in infested leaves but not in water stressed leaves. Proline was the most abundant amino acid and its levels significantly increased by both biotic and abiotic stresses. Proline levels in infested leaves were significantly higher than the water stressed leaves. Histidine, methionine, asparagine, arginine, serine, and leucine levels also increased significantly in infested leaves, but in water stressed leaves only leucine, methionine, and threonine increased. Levels of amino acids, such as tyrosine, isoleucine, phenylalanine, glutamic acid, and alanine, declined in infested leaves. Under water stress asparagine, phenylalanine, serine, and histidine also declined compared to controls. This indicates that while proteolysis occurred under both stresses, metabolic conversion of amino acids was different under the two stresses. In ACP infested leaves some amino acids may be used as feeding material and/or converted into secondary metabolites for defense.